A simple and efficient sample preparation for taxanes in Taxus chinensis needles with natural menthol‐based aqueous deep eutectic solvent. Issue 7 (14th April 2020) - Fan, Xiao‐Hong; Chang, Yuan‐Hang; Wang, Li‐Tao; Zhu, Ya‐Wei; Dong, Ming‐Zhu; Lv, Mu‐Jie; An, Juan‐Yan; Yang, Qing; Jiao, Jiao; Meng, Dong; Fu, Yu‐Jie
Abstract: Taxanes are natural anticancer constituents, and the sample preparation from matrix normally depends on organochlorine solvents. In this study, green and natural menthol‐based aqueous deep eutectic solvent was synthesized and used for sample preparation for taxanes. Five key parameters were optimized and the optimal preparation conditions were as follows: menthol/1‐propanol ratio 1:1 (mol/mol), solid–liquid ratio 1:30 g/mL, extraction time 30 min, ultrasonic power 250 W, and water content 80%. Under the above conditions, the total extraction efficiency of seven main taxanes was 1.25‐ to 1.44‐fold to the conventional methods. In addition, a high‐performance liquid chromatography method with C18 column was established for quantitation of seven main taxanes in <25 min, which had excellent linearity ( R 2 > 0.9986), precision (relative standard deviation < 3.00%), repeatability (relative standard deviation < 3.69%), and recovery (90.26–109.00%). This method performed the extraction, and enrichment processes simultaneously, and it had advantages such as high extraction efficiency, simple operation, low cost, and eco‐friendliness. This work indicated that the natural menthol‐based deep eutectic solvent aqueous could be an excellent alternative to the sample preparation from Taxus or other plants.